Marriage behavior response to prime-age adult mortality: Evidence from Malawi - Ueyama, Mika; Yamauchi, Futoshi (Duke University Press, 2009)
This article examines the effect of AIDS-related mortality of the prime-age adult population on marriage behavior among women in Malawi. A rise in prime-age adult mortality increases risks associated with the search for a marriage partner in the marriage market. A possible behavioral change in the marriage market in response to an increase in prime-age adult mortality is to marry earlier to avoid exposure to HIV/AIDS risks. We test this hypothesis by using micro data from Malawi, where prime-age adult mortality has drastically increased. In the analysis, we estimate the probability of prime-age adult mortality that sample women have observed during their adolescent period by utilizing retrospective information on deaths of their siblings. Empirical analysis shows that excess prime-age adult mortality in the local marriage market lowers the marriage age for females and shortens the interval between the first sex and first marriage.